Efectos del debate en el desarrollo de competencias para el área desarrollo personal ciudadanía y cívica en estudiantes de segundo de secundaria de la Institución Educativa Serafín Filomeno, Iquitos 2022 - Gonzales Romero, Angelica Leonor Guadalupe (2023)
The general objective of the research was to determine the effect of the Debate on the Development of competences for the Personal Development, Citizenship and Civics area in second-year students of the Serafin Filomeno Educational Institution of Iquitos in the year 2022, given the effects and results obtained to validate the application of the debate as a learning strategy in the development of student competencies. The research was of the application type, with an experimental method of the pre-experimental type and its design was quasiexperimental: pre-test and post-test design with a single group. The population was made up of 132 second-year high school students from the Citizenship and Civic Personal Development area of the I.E. Serafin Filomeno from Iquitos enrolled in the year 2022, and the sample selection was the intentional non-random one extracted from the sample design for populations of less than 1500 where a total of 45 students were obtained. For the analysis and interpretation of the data, the student's t hypothesis test was obtained, where tc = 12.7545 was obtained; tt = 2.4141; noting that tc > tt accepting the general hypothesis of the investigation: The effect of the Debate will be statistically significant in the Development of competences for the area of Personal Development, Citizenship and Civics in second-year students of the Serafín Filomeno Educational Institution of Iquitos in the year 2022. In the results before the application of the Debate, a low average of 7.95 was obtained in the Development of competencies in students, and after the application of the Debate, a high average of 16.93 was obtained in the Development of competencies in students, observing a difference of 8.98 points between the pretest and the posttest. It is concluded that the Debate is statistically significant in the Development of competences for the area of Personal Development, Citizenship and Civics in students.